Developing a framework of minimum standards for the risk assessment of alien species. Issue 2 (16th November 2017) - Roy, Helen E.; Rabitsch, Wolfgang; Scalera, Riccardo; Stewart, Alan; Gallardo, Belinda; Genovesi, Piero; Essl, Franz; Adriaens, Tim; Bacher, Sven; Booy, Olaf; Branquart, Etienne; Brunel, Sarah; et al.
Abstract: Biological invasions are a threat to biodiversity, society and the economy. There is an urgent need to provide evidence‐based assessments of the risks posed by invasive alien species (IAS) to prioritize action. Risk assessments underpin IAS policies in many ways: informing legislation; providing justification of restrictions in trade or consumer activities; prioritizing surveillance and rapid response. There are benefits to ensuring consistency in content of IAS risk assessments globally, and this can be achieved by providing a framework of minimum standards as a checklist for quality assurance. From a review of existing risk assessment protocols, and with reference to the requirements of the EU Regulation on IAS (1143/2014) and international agreements including the World Trade Organisation, Convention on Biological Diversity and International Plant Protection Convention, coupled with consensus methods, we identified and agreed upon 14 minimum standards (attributes) a risk‐assessment scheme should include. The agreed minimum standards were as follows: (1) basic species description; (2) likelihood of invasion; (3) distribution, spread and impacts; (4) assessment of introduction pathways; (5) assessment of impacts on biodiversity and ecosystems; (6) Assessment of impact on ecosystem services; (7) assessment of socio‐economic impacts; (8) consideration of status (threatened or protected) of species or habitat under threat; (9) assessment of effects of future climate change; (10) completion possible even when there is a lack of information; (11) documents information sources; (12) provides a summary in a consistent and interpretable form; (13) includes uncertainty; (14) includes quality assurance. In deriving these minimum standards, gaps in knowledge required for completing risk assessments and the scope of existing risk assessment protocols were revealed, most notably in relation to assessing benefits, socio‐economic impacts and impacts on ecosystem services but also inclusion of consideration of climate change. Policy implications . We provide a checklist of components that should be within invasive alien species risk assessments and recommendations to develop risk assessments to meet these proposed minimum standards. Although inspired by implementation of the European Union Regulation on invasive alien species, and as such developed specifically within a European context, the derived framework and minimum standards could be applied globally.